CO2 EMISSION FROM COMBUSTION OF LIGNITE, WASTE PLASTICS AND BIOMASS MIXTURE PELLETS - Duranay, Neslihan Deveci (Assoc Chemical Eng, 2019)
Combustion is a familiar technique for disposal of urban wastes such as plastics when their recycling is impractical. It offers energy recycling and waste diminution. In this paper, combustion behaviours of blend pellets composed of binary and triple mixtures of plastic wastes, biomass and lignite in a laboratory-scale fixed-bed combustion system were examined. The materials chosen as waste plastic, biomass and lignite were, respectively, market plastic bags, furniture plant waste powder and Bingol Karliova lignite. The effect of varied blend pellet composition on the combustion behaviour and CO2 emission in flue gas during combustion was examined. It was observed that the rate and efficiency of combustion increased with increasing plastic ratio in the blend pellets. It was found that the amount of carbon increased with the ratio of waste plastics added to blends, which also increased the CO2 ratio in the flue gas during the volatile matter combustion period. It was concluded that burning waste plastic bags with low-quality lignite or waste biomass could be a viable option to get rid of them and to gain energy.
Emisija CO2 pri sagorevanju peleta na bazi mešavina lignita, otpadne plastike i biomase
Keywords: waste plastic; biomass; lignite; co-combustion; flue gas